ENHANCING TEACHERS SELF-EFFICACY : THEORETICAL AND RESEARCH CONSIDERATIONS - Fatmir Vadahi; Jonida Lesha (European Scientific Journal, ESJ, 2015)
Self-efficacy construct represents a viable organizing concept for the development of new and better professional development models. Selfefficacy is a central feature of social learning theory and its role as a potent intervening factor between learning and subsequent performance has been established by research in a number of contexts, including teacher development. Also self-efficacy construct can provide schools and staff development specialists with the tools they need to design effective teacher trainings, improve teacher competences and as a consequence enhance students outcomes. The purpose of this paper is to give a theoretical analysis to the enhancement of teachers self- efficacy. This study examines different theories on teacher self-efficacy and also gives an overview of what kind of measurements should be taken to enhance teachers self- efficacy